Sobre la teoría materialista del castigo: Una réplica a la tesis de la heterogeneidad interpretativa - Gatti Carlo; Jiménez-Franco Daniel (OSPDH Universidad de Barcelona, 2025)
The aim of this study is to critically address a recurring tendency – here called ‘thesis of the interpretative multiplicity’ – regarding the dominant accounts of the theories of punishment referable to the Marxist tradition. Taking David Garland as the most prominent figure of this trend, we do not intend to deploy an argument as comprehensive as the one under critique. Less ambitiously, what we seek to question is the supposed epistemic opposition between Marxist approaches to punishment, exemplified by Garland’s juxtaposition between Pašukanis’s theory, on the one hand, and that of Rusche and Kirchheimer, on the other. In a re-reading of these authors –while leaving aside theoretical disputes beyond the scope of this paper – our point is that any claim of multiple Marxist theories of punishment should not rest on purely external aspects, but rather on the proven impossibility of reuniting different contributions under common denominators, these being also the constitutive ones of the theoretical tradition of reference. Our conclusion is that an epistemic complementarity between these two theories exists, not only in terms of mere compatibility, but also for an identity of analytical categories and argumentative steps.